Microplastic pollution in edible marine fish from the northwestern Bay of Bengal, Bangladesh: A comprehensive assessment of occurrence, characteristics and associated ecological risks - Zaman, Maria; Haque, Ihsanul; Hasan, Md. Mahmud; Chowdhury , Abdullah Fahim; Billah, Md. Baki; Faruque, Md. Hasan (Journal of Fisheries, 2026)
Microplastic (MP) pollution is an emerging environmental issue with serious implications for marine ecosystems and potential risks to human health. This study assessed MP contamination in the gastrointestinal tracts of 130 individuals representing 13 species (n=10 species–1) from the Bay of Bengal, Bangladesh. A total of 892 MP particles were detected, confirming ubiquitous contamination across all species. MP abundance ranged from 3.70–12.00 items per individual (mean±SD: 6.87±1.08 items fish–1). Five morphotypes: fibers, films, foams, pellets, and fragments were identified, with fibers constituting the dominant category. Most MPs were <5 mm, and red was the most common color. MP abundance exhibited a moderate positive correlation with body length (r=0.41), indicating that larger individuals tended to contain higher numbers of MP. Benthopelagic species exhibited the highest MP ingestion (7.85±2.58 items fish–1), while carnivorous fishes showed greater contamination (7.13±2.59 items fish–1) among trophic guilds. Risk assessment revealed that contamination factor (CF) ranged from 1.00–3.24, indicating moderate to high levels of MP contamination. The overall polymer load index (PLI) was 1.76, corresponding to a low pollution risk category. However, polymer hazard index (PHI) analysis revealed dominance of moderate-risk polymers, including polyester and PP–PE copolymer, with high-risk polymers such as nylon (PHI = 8.80) and PVC (PHI = 7.00) contributing substantially to overall hazard. These findings provide baseline evidence of MP contamination in Bangladeshi marine fisheries and highlight the need for future studies integrating polymer toxicity, trophic transfer, and human exposure pathways to support effective mitigation strategies.